Pyrimidine: a review on anticancer activity with key emphasis on SAR - Aastha Mahapatra; Tanya Prasad; Tripti Sharma (SpringerOpen, 2021)
Abstract Background Cancer is a global health challenge, it impacts the quality of life and its treatment is associated with several side effects. Resistance of the cancer cells to the existing drugs has led to search for novel anticancer agents. Pyrimidine, a privileged scaffold, is part of living organisms and plays vital role in various biological procedures as well as in cancer pathogenesis. Due to resemblance in structure with the nucleotide base pair of DNA and RNA, it is recognized as valuable compound in the treatment of cancer. Main text Many novel pyrimidine derivatives have been designed and developed for their anticancer activity in the last few years. The present review aims to focus on the structure activity relationship (SAR) of pyrimidine derivatives as anticancer agent from the last decade. Conclusion This review intends to assist in the development of more potent and efficacious anticancer drugs with pyrimidine scaffold. Graphical abstract